Relationship between level of education and continuity of leprosy treatment in Brazil from 2017 to 2022 (Research, Society and Development, 2023)
Objective: To investigate the relationship between the level of schooling of leprosy patients in Brazil and continuity of treatment in the period from 2017 to 2022. Methodology: It consists of a quantitative descriptive epidemiological study carried out through data collected from the Departamento de Informática do Sistema Único de Saúde (DATASUS). The variables analyzed were the number of doses for treatment of paucibacillary and multibacillary leprosy applied in the analyzed period according to schooling, year, and state. The collected data were tabulated and stored in the Google Spreadsheets program for later availability in absolute and relative frequencies of the results. Results: The results revealed a significant correlation between the level of education and the continuity of treatment for leprosy. In total, 1.529.590 patients diagnosed with multibacillary leprosy and 265.442 with paucibacillary leprosy were reported and treated. A pattern emerged in which both types of the disease showed a prevalence of patients who had an educational level of incomplete primary education (1st to 4th grade). Notably, there was a higher prevalence of the disease in the northeastern region, with 41.97% of cases treated as paucibacillary and 45.61% as multibacillary. Conclusion: There is a direct relationship between the level of education, incidence and continuity of leprosy treatment in Brazil. Therefore, we note the possibility of a concern with a pathology that, even with treatment, remains present.